Ultrastructural features of psychological stress resilience in the brain: a microglial perspective - Fernando González Ibáñez; Jared VanderZwaag; Jessica Deslauriers; Marie-Ève Tremblay (Open Biology)
Psychological stress is the major risk factor for major depressive disorder. Sustained stress causes changes in behaviour, brain connectivity and in its cells and organelles. Resilience to stress is understood as the ability to recover from stress in a positive way or the resistance to the negative effects of psychological stress. Microglia, the resident immune cells of the brain, are known players of stress susceptibility, but less is known about their role in stress resilience and the cellular changes involved. Ultrastructural analysis has been a useful tool in the study of microglia and their function across contexts of health and disease. Despite increased access to electron microscopy, the interpretation of electron micrographs remains much less accessible. In this review, we will first present microglia and the concepts of psychological stress susceptibility and resilience. Afterwards, we will describe ultrastructural analysis, notably of microglia, as a readout to study the mechanisms underlying psychological stress resilience. Lastly, we will cover nutritional ketosis as a therapeutic intervention that was shown to be effective in promoting psychological stress resilience as well as modifying microglial function and ultrastructure.